مكانة الأرض في القرآن والسنة على ضوء المقاصد الشرعية - Mohamed Fathy, Mohamed Abdelgelil; Mohd A'tarahim, Mohd Razali; Najmiah, Omar; Rohaizan, Baru; Tasnim, Abdul Rahman (2019)
In the age of technology and progress many individuals seek to gain from undertaking online commerce and marketing, through opening commercial site shops or others. This is undoubtedly desirable, but in this research I want to draw attention to one of the old course of gaining, that humankind is still in need of, even urged by the wise law in the Qur’an and Sunnah, namely the reclamation of the uncultivated lands, and this is one of the basics of legitimate gain, and it follow from this research that exerting effort in this reclamation realize the purposes of Shariah in terms of benefiting Muslims with development and urbanization, as well as realizing the vicegerency of man on earth, and through all these the purpose of justice in Islamic law is achieved by fair distribution of the sources of production and by cutting off the exploitation of the weak by the bourgeois and entrepreneurs and ensuring distributive justice of public funds. Thus money is traded between individuals in a manner that realizes justice and reduces the difference in classes. And it is known that one of the purposes of shari‘ah in reclamation is to convert the lands that are favorable to productive force. Therefore, whoever violates this, for deficiency or negligence, his ownership to this land will be sanctioned. In order to achieve public interest, it is not permissible to reclaim lands that benefiting the public such as roads, pastures, water pool and lest there is wrangle among people there should have permission from imam before reclaiming.